THE ROLE OF FOREIGN DIRECT INVESTMENTS (FDI) AS A PROMOTER OF GROWTH – ATTRACTIVENESS OF ALBANIA FOR FDI - Berberi (Mirashi), Alba (European Scientific Journal, ESJ, 2013)
Foreign direct investments (FDI) are playing an important role in the economic background of the Transition Economies. They are a catalyst of the economic growth and of the technological development, when domestic savings cannot. Many countries have benefited from capital inflows in the form of FDI. Fighting the lack of capital that the closed markets used to suffer, they have helped the effective use of these sources and they have created a competitive environment, which provides the investors with ever-growing outputs. So, considering that foreign investments are a very important asset to transition economies, the aim of this paper is to provide a general view of the role and determinants of foreign direct investments, an overview of foreign direct investments in Albania and especially, providing some suggestions to attract foreign investors (the case of foreign investors in textile industry in Albania).